2004
DOI: 10.1159/000081883
|View full text |Cite
|
Sign up to set email alerts
|

Survey among Surgeons on Surgical Treatment Strategies for Secondary Peritonitis

Abstract: Background: There is controversy about performing either a planned relaparotomy (PR) or relaparotomy on demand (ROD) in patients with secondary peritonitis. Subjective factors influencing surgeons in decision making for either surgical treatment strategy have never been studied. Methods: All 858 surgeons of the Association of Surgeons of The Netherlands were sent a survey with 16 case vignettes simulating peritonitis patients and evaluating the preference for PR or ROD. Results: Sixty-two percent of surgeons r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
(18 reference statements)
0
10
0
5
Order By: Relevance
“…More than half of the surgeons performed at least 25% GI operations yearly; although 90% indicated that they performed other operations as well. Surgeon characteristics have previously been described in detail [19]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More than half of the surgeons performed at least 25% GI operations yearly; although 90% indicated that they performed other operations as well. Surgeon characteristics have previously been described in detail [19]. …”
Section: Resultsmentioning
confidence: 99%
“…Accurate and timely selection of patients for relaparotomy is a prerequisite for improvement of the treatment of secondary peritonitis, especially regarding the growing popularity of the on-demand relaparotomy strategy compared to other relaparotomy strategies [3, 4, 19,27,28,29,30]. Particularly the on-demand strategy encompasses extensive monitoring and multidisciplinary care with frequent radiological imaging and adjustments of treatment policy at every stage of the acute disease, as this strategy harbors the risk of a potentially harmful delay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age was 69 years (IQR, 58-75 years), 48% were men, and the median APACHE-II score was 15 (IQR, [13][14][15][16][17][18]. The most common cause for peritonitis was gastrointestinal perforation (58%).…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…There is consensus that the preferred strategy for mild peritonitis (APACHE-II [Acute Physiology and Chronic Health Evaluation] score of Յ10) is on-demand relaparotomy. 4,[12][13][14] Despite lacking evidence from randomized trials, overall support for the on-demand strategy even among patients with severe peritonitis is growing, 4,12,13,15,16 but both strategies are still used side-by-side in clinical practice. 17,18 The debate on which strategy is preferred dates back as far as the call for a randomized trial comparing both strategies by the Joint Working Party of the North American and European Surgical Infection Society in 1990.…”
mentioning
confidence: 99%